Briefing Note: The legal rule that computers are presumed to be operating correctly – unforeseen and unjust consequences. (2022) - Bohm, Nicholas; Christie, James; Ladkin, Peter Bernard; Littlewood, Bev; Marshall, Paul; Mason, Stephen
No abstract available